Pattern Of Aid Giving. - Neumayer, Eric (Routledge, 2003)
Using econometric analysis, the author examines factors that determine patterns of aid giving including aggregate aid flows, aid from multilateral organisations and aid from bilateral donors such as Germany, Japan, the US and Arabia.